Okul Yöneticilerinin Liderlik Stilleri ile Okulların Öğrenen Örgüt Olma Düzeyi Arasındaki İlişki - Akan, Durdağı; Sezer, Şenol (Fırat University, 2014)
ÖzetOkul yöneticilerinin liderlik stilleri ile okulların öğrenen örgüt olma düzeyi arasındaki ilişkiyi belirlemek amacıyla gerçekleştirilen bu araştırmada, ilişkisel desen ve nicel araştırma yöntemi kullanılmıştır. Araştırmanın çalışma grubu 2012-2013 eğitim öğretim yılında, Trabzon il merkezindeki 14 lisede görevli, 1070 öğretmen arasından tabakalı örneklem alma yöntemiyle belirlenen 240 öğretmenden oluşmaktadır. Araştırmada veri toplama aracı olarak, çok faktörlü liderlik stilleri ölçeği (MLQ) ve örgütlerde öğrenen organizasyon disiplinlerinin gerçekleşme düzeyini belirleme ölçeği kullanılmıştır. Araştırma grubunun anket maddelerine verdiği yanıtlar sayısallaştırılarak, frekans, yüzde, ortalama, standart sapma değerleri analiz edilmiştir. Değişkenlere ilişkin puanlar arasındaki farklılıkları belirlemede Bağımsız t Testi, ölçeklerden elde edilen puanlar arasındaki ilişkilerin saptanmasında Pearson Çarpım Momentler Korelâsyon Analizi, okul yöneticilerinin liderlik stilleri ile okulların öğrenen örgüt olma düzeyi arasındaki ilişkiyi belirlemede ise Çoklu Doğrusal Regresyon Analizi tekniklerinden yararlanılmıştır.Regresyon analizi sonuçlarına göre, okul müdürlerinin dönüşümcü liderlik davranışları ile okulların öğrenen örgüt olma düzeyleri arasında pozitif yönde ve yüksek düzeyde istatiksel olarak anlamlı bir ilişki [r= .76, p< .01] görülmektedir.

The purpose of this study is to determine the relationship between becoming a learning organization level of the schools and the principals' leadership styles. The study was designed in quantitative research model, and the relational patterns were used. The study was conducted on 240 teachers were determined by using stratified sampling method among 1070 teachers who serve in 14 high schools in Trabzon province in 2012-2013 academic year. As a data collection instrument the Multifactor Leadership Styles Questionnaire (MLQ) which developed by Bass and Avolio and adapted to Turkish by Akdoğan and the Scale to Determine the Realization Level of the Learning Organization Disciplines in the Organization developed by Türkoğlu were used in the study. The responses of the participants to the questionnaire were digitized and the values of the frequency, percentage, mean and standard deviation were analyzed. Independent t-test was used to determine differences between scores on the variables, Pearson Product Moment Correlation Analysis was used to determine the relationship between the scores obtained from the scales and Multiple Linear Regression Analysis techniques were used to determine the relationship between the school managers' leadership styles and the levels of becoming a learning organization of the schools. According to the results of the regression analysis, between the school principals' transformational leadership behaviours and becoming learning organization levels of the schools a high level statistically significant positive correlation [r =.76, p <.01] is seen
Relation between the Principals’ Leadership Styles and Becoming a Learning Organization Level of the Schools